The Volume Status among Hyponatremic admitted Patients: Assessment of Volume Status in Hyponatremic Patients in Tertiary Care Hospital - Memon, Shoukat (Pakistan Journal of Kidney Diseases, 2024)
Introduction: The kidneys play a vital role in the management of hyponatremic patients with fluid disturbances. This task becomes more challenging in presence of comorbidities like chronic kidney disease or congestive heart failure. Accurate assessment of volume status and urinary sodium excretion is essential part for the correct management.. Both impaired renal function and compromised left ventricular function complicate the accurate evaluation of a patient's fluid status. Method: This cross-sectional prospective study was conducted over 262 adult patients with hyponatremia at The Indus Hospital, Karachi from 2017 to 2020. The patient's volume status at the time of enrollment was categorized as normovolemic, hypovolemic, or hypervolemic based on clinical examination. Spot urine sodium, chloride, potassium, urine and serum osmolality, serum urea, and Random blood sugar were all done. Results: There was a total of 262 patients in which 123 (46.9%) were male and 139 (53.1%) were female. The mean age was 54.1 ± 16.4 years. The overall comorbid burden was high 227(86.64%), in which hypertension and CKD contributed more. Out of 262 patients, half of them suffered from hypovolemia 131(50%). Spot urine sodium (>20 meq) was found in 219(83.58/%) patients, in which predominant volume status was hypovolemia 104(47.5%). Moreover, among those who could not survive were 28 (10.7%), in which hypovolemia contributed more than other volume status 12(42.85%). Conclusion: Hypovolemia came out to be the predominant volume status among hyponatremic patients with high comorbid burden. Majority excreted more sodium in spot urine sample despite of hypovolemia in majority.